2019
DOI: 10.1111/bjd.18442
|View full text |Cite
|
Sign up to set email alerts
|

The cost of childhood atopic dermatitis in a multi‐ethnic Asian population: a cost‐of‐illness study

Abstract: Summary Background Childhood atopic dermatitis can often have a negative impact on quality of life for affected children and their caregivers. The condition contributes to increased healthcare costs and can pose heavy economic burdens on healthcare systems and societies. Objectives The objective of this study is to provide a comprehensive estimate of the economic burden of childhood atopic dermatitis in a Singaporean sample and to investigate associated factors. Methods This cross‐sectional cost‐of‐illness stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 32 publications
4
24
0
Order By: Relevance
“…Similar cost estimates have been published for AD in Singapore, 16 the Asia Pacific region, Thailand, South Korea and Vietnam 17 . Understandably, cost increases with disease severity 12,14,16 …”
supporting
confidence: 62%
“…Similar cost estimates have been published for AD in Singapore, 16 the Asia Pacific region, Thailand, South Korea and Vietnam 17 . Understandably, cost increases with disease severity 12,14,16 …”
supporting
confidence: 62%
“…The study showed that the economic burden of childhood AD is mostly attributed to informal caregiving (personal care, preparing special meals and providing emotional support) and out‐of‐pocket expenses (purchased products such as moisturizing creams and hygiene products, and laundry costs) . The study findings suggest the need for policies to reduce the burden of informal caregiving and financial strain on families . Some aspects of caregiving can be aided by a range of supportive services to meet the holistic needs of patients and carers, including psychological support, access to social workers and occupational therapy .…”
mentioning
confidence: 93%
“…AD, characterized by symptoms of itchiness, sleep disturbances, pain, physical changes to the skin, anxiety and loss of productivity (through absenteeism), is associated with a marked impairment of quality of life . The condition often requires regular application of moisturizers, avoidance of triggering factors, out‐of‐pocket expenses and informal caregiving (for children and the elderly) . In more severe cases, regular visits to specialist centres (for phototherapy or drug monitoring), attendance in the emergency department and inpatient admission may be required .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is difficult to quantify the full economic burden of AD, the indirect costs of atopic diseases can exceed direct costs [3]. Several studies have attempted to quantify the QoL and direct/indirect economic burden of AD [3][4][5][6]. However, these estimates may not capture the more intangible disease-related burden and associated economic burden.…”
Section: Introductionmentioning
confidence: 99%